IMPLEMENTATION OF FINANCING RESTRUCTURING IN ISLAMIC BANKING DURING THE COVID-19 PANDEMIC IN INDONESIA - Rusli Siri (Sean Institute, 2023)
This research is motivated by the impact of the Covid-19 pandemic on the Indonesian nation. Covid-19 has an impact on business activities in general. This is the reason why the government's policy of restructuring financing for Islamic banks during the Covid-19 pandemic has emerged. The Covid-19 outbreak that has infected almost all parts of the world has an impact on all dimensions, be it social, political, or economic. The impact in terms of the economy on Islamic financial institutions is problematic financing. The resulting problematic financing has the potential to disrupt banking performance and financial system stability, which can affect economic growth. This study aims to find out the extent of how the implementation of financing restructuring in Islamic banking. In addition, to find out whether restructuring is felt to be beneficial for business people. This research uses a qualitative type of research with a case study approach using data collection techniques through observation, and literature (library research). Based on the results of the study, it can be seen that Sharia Banks in providing financing restructuring to customers due to the Covid-19 Pandemic are based on the Financial Services Authority Regulation Number 16 / POJK.03 / 2014, which can only be given to customers who have difficulty fulfilling their obligations to banks due to their business being affected by Covid-19. In addition, the study also found that restructuring began with rescheduling, reconditioning, and, restructuring. All these stages are carried out in order to fulfil the purpose of a customer's initial contract with the bank, namely to give birth to a legal consequence or common intention that is intended and that the party wants to realize through the making of an agreement. Because the contract in the law of engagement means binding, for which a debtor is obliged to complete the payment of instalments until a predetermined time limit in accordance with the agreement. This study concluded that the practice of financing restructuring was carried out as an effort to save problematic financing. The implementation of restructuring, when viewed from the POJK, especially POJK 48, shows several important points that banks must consider. In addition, the implementation of the restructuring pays attention to the DSN MUI Fatwa No. 47,48,49, regarding the settlement of non-performing financing, the absence of additional costs, and the conversion of contracts. The restructuring period varies greatly depending on the Islamic bank's assessment of its customers.